Hubungan perilaku caring perawat dengan tingkat kepuasan pasien rawat inap di Rumah Sakit - Pakpahan, Hetti; Hutabarat, Swandi; Silalahi, Detty; Devi, Devi (JOURNAL OF Mental Health Concerns, 2025)
Background: The attitude and service of human resources, especially nurses, have a significant influence on the success of hospital services in addition to the completeness of facilities. Indicators of the quality of service provided in hospitals include compassionate behavior which is very important in nursing practice. Compared to nurses who do not care, those who show compassion are four times more likely to make their patients happy. When nurses are indifferent, patients often feel dissatisfied. Patients complain about the services they receive, which can be detrimental to the hospital. Purpose: To determine the relationship between inpatient satisfaction nurse caring behavior. Method: A descriptive correlation, the population of this study was 302 patients who were treated in the inpatient ward from February to March 2024. The study sample consisted of 30 people who were selected randomly. The chi-square test was used to analyze the data.  Results: showed a p value of 0.001 p <0.05 there was a correlation between the level of patient satisfaction at and the compassionate behavior of nurses. Conclusion: Patient satisfaction can increase if nurses behave compassionately. Keywords: Conduct; Contentment; Nurse; Nursing; Patient.   Pendahuluan: Sikap dan pelayanan sumber daya manusia, khususnya perawat, memiliki pengaruh yang signifikan terhadap keberhasilan pelayanan rumah sakit selain kelengkapan fasilitas. Indikator mutu pelayanan yang diberikan di rumah sakit antara lain perilaku penuh kasih sayang yang sangat penting dalam praktik keperawatan. Dibandingkan dengan perawat yang tidak peduli, mereka yang menunjukkan rasa kasih sayang memiliki peluang empat kali lebih tinggi untuk membuat pasiennya senang. Ketika perawat bersikap acuh tak acuh, pasien sering kali merasa tidak puas. Pasien mengeluhkan pelayanan yang diterimanya, yang dapat merugikan rumah sakit. Tujuan: Untuk mengetahui hubungan antara kepuasan pasien rawat inap dengan perilaku caring perawat. Metode: Korelasi deskriptif. Populasi penelitian ini adalah 302 pasien yang dirawat di ruang rawat inap pada bulan Februari sampai dengan Maret 2024. Sampel penelitian berjumlah 30 orang yang dipilih secara acak. Uji chi-square digunakan untuk menganalisis data. Hasil: penelitian menunjukkan nilai p sebesar 0.001 p <0.05 terdapat korelasi antara tingkat kepuasan pasien dengan perilaku perawat yang penuh kasih sayang. Simpulan: Kepuasan pasien dapat meningkat apabila perawat berperilaku penuh kasih sayang. Kata Kunci: Keperawatan; Kepuasan; Pasien; Perawat; Perilaku.